Product Development of Unique Clothing Learning Media to Stimulate Fine Motor Skills of 4-5 Years Old Children - Heni Nopiyanti; Imam Tabroni; Uwe Barroso; Amina Intes (Journal of Computer Science Advancements, 2023)
The purpose of this study was to create a learning model product in the form of unique clothing to stimulate fine motor skills of children aged 5-6 years in Purwakarta. The research method used a mixed method with a research and development (R&D) design. The research process starts from making a product design design using media with materials around, in the form of used gallon bottles, design validation, revision, making products, limited product trials, making products, stage 1 product revision, main field trials, revision 2, operational field trials, product revision 3, dissemination and product marketing. The results of research on the development of unique clothing learning models to stimulate fine motor skills are more creative and innovative learning models. The results of the research in the form of children's fine motor movement skills are getting better and children's fine muscles are getting stronger and more skillful. This unique clothing model gives children the interest to be able to play it so that fine motor skills are stimulated in a fun way. The technique supports children's understanding of attitudes, motivation and curiosity towards psychomotor activities (fine motor). This broad trial was conducted three times and experienced good improvement, so it is hoped that this model can be disseminated to PAUD institutions in Purwakarta and surrounding areas.